2012
DOI: 10.3758/s13421-012-0229-x
|View full text |Cite
|
Sign up to set email alerts
|

Looking like a criminal: Stereotypical black facial features promote face source memory error

Abstract: The present studies tested whether African American face type (stereotypical or nonstereotypical) facilitated stereotype-consistent categorization, and whether that categorization influenced memory accuracy and errors. Previous studies have shown that stereotypically Black features are associated with crime and violence (e. here, we extended this finding to investigate whether there is a bias toward remembering and recategorizing stereotypical faces as criminals. Using category labels, consistent (or inconsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 33 publications
(47 reference statements)
4
58
2
Order By: Relevance
“…First, Experiment 1 replicates work (e.g., Cassidy et al, 2012; Kleider et al, 2012; Nash et al, 2010) showing better memory for congruent over incongruent face-behavior pairs, while uniquely showing that congruent and incongruent pairs are better remembered than pairs with average faces. This suggests that even when appearance and behavioral cues conflict, they improve memory beyond when receiving less information.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…First, Experiment 1 replicates work (e.g., Cassidy et al, 2012; Kleider et al, 2012; Nash et al, 2010) showing better memory for congruent over incongruent face-behavior pairs, while uniquely showing that congruent and incongruent pairs are better remembered than pairs with average faces. This suggests that even when appearance and behavioral cues conflict, they improve memory beyond when receiving less information.…”
Section: Discussionsupporting
confidence: 54%
“…Recent work (Cassidy, Zebrowitz, & Gutchess, 2012; Kleider, Cavrak, & Knuycky, 2012; Nash et al, 2010; Rule, Slepian, & Ambady, 2012; Suzuki & Suga, 2010) explored appearance-behavior congruity effects in memory. Creating congruent (e.g., trustworthy face/positive behavior) and incongruent (e.g., trustworthy face/negative behavior) face-behavior pairs can lead to memory biases for both congruent (e.g., Nash et al, 2010) and incongruent (e.g., Suzuki & Suga, 2010) information.…”
mentioning
confidence: 99%
“…Previous work (Kleider et al, in press; Nash et al, 2010; Suzuki & Suga, 2010) has shown that facial characteristics can bias source monitoring, particularly when facial characteristics mismatch actor behaviors (e.g., misattributing an implausible newspaper headline to an untrustworthy-looking source). The present studies extend this literature by using the babyface stereotype, and reveal that if a person looks dominant, that person will be remembered as dominant over a person whose facial characteristics convey submissiveness, even if previous behaviors say otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not directly ask participants to form impressions, the automaticity of stereotyped impressions from facial cues biased source monitoring. Another recent study demonstrated that regardless of race or gender, the similarity between facial features and stereotyped categories also bias source memory, such that individuals with more stereotypically Black features are more likely to be misremembered as criminals than non-stereotypical faces (Kleider, Cavrak, & Knuycky, in press). Additionally, Suzuki and Suga (2010) found that after playing an economic game, participants identified more trustworthy than untrustworthy looking cheaters, suggesting that face-behavior incongruity increased encoding of impressions into memory, perhaps because memory for potentially misleading trustworthiness could protect people in certain situations.…”
mentioning
confidence: 99%
“…Kleider, Cavrak, and Knuycky (2012) paired faces that were either high or low on perceived Black stereotypicality with category labels that were either consistent (i.e., drug dealer) or inconsistent (i.e., artist and teacher) with stereotypes about Blacks. After studying these face-label pairings, participants were shown each face individually and asked to indicate the category label with which the face had initially been paired.…”
Section: Direct Support For the Contextual Model Of Eyewitness Identimentioning
confidence: 99%